An accurate non-Born–Oppenheimer calculation of the first purely vibrational transition in LiH molecule - Bubin, Sergiy; Adamowicz, Ludwik; Molski, Marcin (American Institute of Physics Publishing, 2005)
In this work we study the ground and the first vibrationally excited states of LiH molecule. We performed an extensive nonrelativistic variational calculations of the two states without using the Born–Oppenheimer approximation. The results are analyzed and compared with the data extracted from recent experiments. The 0←1 transition energy obtained in the calculations converged to a value which is less than a wave number above the transition energy estimated from the available experimental data concerning the LiH rovibrational transitions. We discuss the remaining discrepancy and the procedure used to determine the “experimental” transition frequencies
Keywords: Physics; LiH molecule